2022
DOI: 10.1021/acsomega.1c06950
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction with Manganese Oxide Nanospheres in Microbial Fuel Cells

Abstract: Operating microbial fuel cells (MFCs) under extreme pH conditions offers a substantial benefit. Acidic conditions suppress the growth of undesirable methanogens and increase redox potential for oxygen reduction reactions (ORRs), and alkaline conditions increase the electrocatalytic activity. However, operating any fuel cells, including MFCs, is difficult under such extreme pH conditions. Here, we demonstrate a pH-universal ORR ink based on hollow nanospheres of manganese oxide (h-Mn 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The monitored pH values are shown in Figure 3a, where it can be seen that the values vary from slightly neutral to slightly acidic, showing an optimal operating pH on day 14 of 7.867 ± 0.147. It has been reported that the pH values of substrates such as vegetables or fruits vary due to fermentation, that each type of substrate will have a different pH, and that environmental conditions are a determining factor for this [39,40]. For this reason, the optimal operating pH of each substrate must be found, so that when this value is found, it can be adjusted in future work and the efficiency of each microbial fuel cell can be optimized [41].…”
Section: Electrical Parameters Measurementmentioning
confidence: 99%
“…The monitored pH values are shown in Figure 3a, where it can be seen that the values vary from slightly neutral to slightly acidic, showing an optimal operating pH on day 14 of 7.867 ± 0.147. It has been reported that the pH values of substrates such as vegetables or fruits vary due to fermentation, that each type of substrate will have a different pH, and that environmental conditions are a determining factor for this [39,40]. For this reason, the optimal operating pH of each substrate must be found, so that when this value is found, it can be adjusted in future work and the efficiency of each microbial fuel cell can be optimized [41].…”
Section: Electrical Parameters Measurementmentioning
confidence: 99%
“…In recent years, polymer electrolyte fuel cells (PEFCs) have been attracting the attention of many research groups as clean energy storage and conversion devices. In order to commercialize transportation from light- to heavy-duty vehicles, especially for high-power applications such as long-haul trucks, trains, buses, and ships, as well as increase the average daily and lifetime mileage of these applications, the durability and performance of PEFCs must be improved . Particularly, the cell voltage reversal occurs when the fuel supplied to the anodes is depleted, leading to a transient dissolution of the platinum (Pt) catalyst and continuous oxidation of carbon, which is used as commercial catalyst support in fuel cells. To replace conventional carbon in the electrodes, corrosion-resistant metal oxide nanoparticles have emerged as potentially suitable candidates. Among them, titanium oxide (TiO 2 ) particles are promising as catalyst support for fuel cell applications because of their chemical and thermal durability as well as abundant resources . However, the poor electrical conductivity of TiO 2 hinders its potential usage as electrocatalyst support.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese oxides (MnO x ) possess the merits of multiple valence states, earth-abundance, inexpensive, and eco-benignity. , Many of them exhibit catalytic ability in electroreduction of nitric oxide (NO), nitrogen oxyanions (NO 2 – /NO 3 – ), , and oxygen, indicating that MnO x has good electrocatalytic reduction activity. In this process, Mn III /Mn II species in MnO x play an important role in promoting the electrocatalytic reduction reaction.…”
Section: Introductionmentioning
confidence: 99%